1996
DOI: 10.1006/viro.1996.0167
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Activation Is Delayed in Mouse L929 Cells Infected with Interferon Suppressing, but Not Inducing, Vesicular Stomatitis Virus Strains

Abstract: Vesicular stomatitis virus (VSV) mutant T1026R1 of the Indiana (IN) serotype is a good inducer of interferon (IFN). This mutant was used to study the activation of NF-kappaB, a transcription factor necessary for IFN induction, in mouse L929 cells that were stably transfected with a chimeric gene containing the human IFN-beta gene promoter attached to the chloramphenicol acetyltransferase (CAT) coding sequence. NF-kappaB DNA binding activity was detected as early as 30 min after virus adsorption in nuclear extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…However, it is also possible that M protein inhibits additional steps in the production of IFNs upstream of the general transcription factor TFIID. For example, the activation of NF-B, one of the factors required for IFN gene transcription, is delayed in cells infected with wt VSV compared to cells infected with the T1026R1 mutant (8). This suggests that the wt M protein delays activation of NF-B, which could play a role in the suppression of IFN gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that M protein inhibits additional steps in the production of IFNs upstream of the general transcription factor TFIID. For example, the activation of NF-B, one of the factors required for IFN gene transcription, is delayed in cells infected with wt VSV compared to cells infected with the T1026R1 mutant (8). This suggests that the wt M protein delays activation of NF-B, which could play a role in the suppression of IFN gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cells capable of producing and responding to alpha/beta interferons, such as chicken embryo cells, the replication of these viruses is severely compromised, particularly at elevated temperatures, so that one of these mutants (tsO82) was originally identified as a ts mutant (40). Infection with viruses containing M gene mutations, such as tsO82 virus, results in production of much more alpha/beta interferon than does infection with the wild-type viruses from which they were derived (15,89), supporting a role for M protein in suppressing the induction phase of the alpha/beta interferon response. There is one example of a VSV mutant in which infected cells produce more alpha/beta interferon than do cells infected with the wild-type strain from which this mutant was derived, yet this mutant does not contain a mutation in its M protein (89).…”
Section: Inhibition Of the Host Antiviral Response By M Proteinmentioning
confidence: 99%
“…A previous report indicated that NF-κB activation is delayed for several hours after wild-type (wt) vesicular stomatitis virus (VSV) infection, while this transcription factor is rapidly activated in L929 cells infected with the T1026R1 (R1) mutant strain of VSV (Boulares et al, 1996). The R1 virus (Stanners et al, 1977) expresses a mutant matrix (M) protein, in which there is methionine-to-arginine substitution at amino acid position 51 (Ferran and Lucas-Lenard, 1997).…”
Section: Introductionmentioning
confidence: 99%